In Vivo Autofluorescence Spectroscopic Study and Evaluation of DNA Damage By Comet Assay in Smokers - Rajmohan, M (J Clin Diagn Res, 2015)
CONTEXT: Tobacco is known environmental factor to alter the chemical composition of cells and the structure of DNA. Cellular level changes of smoker’s mucosa are assessed by autofluorescence spectroscopy and the DNA damage can be evaluated by single cell gel electrophoresis (comet assay). AIM: To substantiate the changes in the autofluorescence due to smoking with that of early DNA damage without any clinical change. MATERIALS AND METHODS: Group I consists of 20 individuals with normal mucosa and Group II consists of 40 individuals with smoking habit. Only males were included in this study and their age ranging from 25 to 35 years. In vivo fluorescence spectra from both groups were obtained by using hand held fiber optic probe attached to Varian Cary Eclipse fluorescence spectrophotometer and comet assay was carried out for normal and smokers by their peripheral blood. STATISTICAL ANALYSIS USED: Independent-Samples t-test was used for statistical analysis. P-value was obtained to discriminate the statistical differences between the two groups. RESULTS: The averaged excitation and emission spectra of normal and smoker’s mucosa showed significant differences statistically. In comet assay, the mean tail length of smoker group was higher than the normal group. The results showed statistically significant differences (p ≤ 0.05). CONCLUSION: These techniques will be very useful for monitoring of very early changes of mucosa before clinical manifestation of the lesion in high risk smokers and thus prevents the occurrence of premalignant disorders and early invasive carcinoma.